Portfolio insurance strategies : a comparison of OBPI versus CPPI - Chen, Xinyi (2011)
This paper provides a performance evaluation of the option-based portfolio insurance (OBPI) using a synthetic put and constant proportion portfolio insurance (CPPI) technique against a passive buy-and-hold strategy. Our study seeks to clarify the effectiveness of portfolio insurance strategies as such strategies become increasingly popular, yet mixed research evidence gives no consensus on their effectiveness. We explore 4 global markets, namely the United States, United Kingdom, Hong Kong and Japan in evaluating the effectiveness of these strategies. Apart from traditional mean-variance performance measures such as Sharpe and Sortino ratio, we consider the Value-at-Risk and Expected Shortfall of the strategies, which are more appropriate in a portfolio insurance context. Our results indicate that portfolio insurance strategies do outperform a buy-and-hold strategy for all 4 market indices. Furthermore, the Sharpe and Sortino ratios indicate that OBPI outperforms CPPI in bullish years and when the market is moderately volatile. Only in situations when the market is extremely volatile does CPPI perform better than OBPI. VaR and Expected Shortfall for OBPI prove to be consistently higher than CPPI, and they are especially high during the volatile periods. Moreover in general, a higher rebalancing ratio and higher floor value outperforms lower rebalancing ratio and lower floor value respectively.